2005
DOI: 10.1002/ptr.1768
|View full text |Cite
|
Sign up to set email alerts
|

Some clinico-pathological changes associated with the aqueous extract of the leaves ofPhyllanthus amarus in rats

Abstract: The pathological changes of the aqueous crude extract of the leaves of Phyllanthus amarus were studied in 32 male rats over a period of 30 days. The animals were divided into four groups of eight animals per group. The aqueous crude extract was prepared and administered orally using a cannula to rats in three groups receiving doses of 400 mg/kg, 800 mg/kg and 1,000 mg/kg but the fourth group served as a control and received distilled water only. Blood samples were collected for haematological and serum biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 9 publications
5
47
1
1
Order By: Relevance
“…The observed increase in total protein levels in the treated animals may suggest that the plant extracts contained essential phytocompounds which help to restore the damaged liver. Apart from being a useful indicator of the integrity of glomerular membrane, albumin also is vital in determining the cruelty of disease (Adedapo et al, 2005). This result is in agreement with the report of the other researchers (Akanbi, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The observed increase in total protein levels in the treated animals may suggest that the plant extracts contained essential phytocompounds which help to restore the damaged liver. Apart from being a useful indicator of the integrity of glomerular membrane, albumin also is vital in determining the cruelty of disease (Adedapo et al, 2005). This result is in agreement with the report of the other researchers (Akanbi, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…It may be inferred from the present results that higher doses of Chanca Piedra may have resulted in degenerative changes observed in the renal cortex. The histological effects observed in this experiment is in coherance with the report of Manjrekar et al who observed that Chanca piedra induced deleterious changes on the renal tubules rats [ 45,46]. It is important to note that Chanca piedra contains alkaloids and lots of antioxidants [7,8,9].…”
Section: Histological Analysissupporting
confidence: 88%
“…The presence of some phytochemicals in the A. wilkesiana leaves extract with the ability to stimulate the production of white blood count and its differentials could be responsible for the observed results in the treated diabetic rats. This observation of increasing levels of these parameters by A. wilkesiana extract suggests that the principal function of phagocytes, which is to defend against invading microorganisms by ingesting and destroying them, thus contributing to cellular inflammatory processes of the animals, will be enhanced [52].…”
Section: White Blood Cells (Wbc)mentioning
confidence: 87%